師資生集中實習教學省思札記之內容分析 A Content Analysis of Reflective Journal Writing: Exploring Prospective Teachers' Reflections on Field Experience During Intensive Practicum - 周鳳美 Chou, Phone-Mei (National Changhua University of Education, 2010)
本文探討四位師資生在教學實習課程集中實習期間的教學省思。藉由分析省思札記的省思主題與省思層次，以瞭解師資生的學習以及省思品質。研究結果顯示：（一）省思主題涵蓋五個範圍：教學方法與教學過程、教學評鑑、輔導老師行為與理念、自我知覺、參考理論與文獻。由各主題的條目數量多寡透露：師資生最重視各科教學方法與教學過程，而甚少聯繫正式知識於教學實務。（二）省思層次出現「描述」、「描述省思」、與「對話省思」。其中，不具備省思特質的「描述」條目，稍多於其他兩項的總和。就省思品質而言，師資生實踐四種省思類型，缺少批判省思；此外，近於一半 的省思條目具建設性省思的性質。基於研究結果，肯定本文實施的省思札記教學策略，並提出改善之處。結論對師培課程提出建議以促進培養師資生省思能力。 The purpose of this study was to explore four preservice teachers' reflections on field experiences in the context of their Teaching Practicum course through the analysis of journal writing. To understand the ways that they learned to teach as well as the quality of reflection among prospective teachers, the researcher examined the topics and the levels of reflection produced by the four preservice teachers. Two major findings emerged. First, topics of reflection fell into five categories: (a) teaching methods and process, (b) evaluating teaching, (c) mentors' performance and ideas, (d) self-awareness, and (e) theories from the literature. These topics reveal that informants pay much more attention to teaching methods and process than to formal knowledge presented in the literature. Second, descriptive writing, descriptive reflection, and dialogic reflection were the three categories of reflective levels that appeared in the preservice teachers' journals. Among them, nonreflective descriptive writing appeared more frequently in their journals than the other two categories. As for the quality of reflection, informants were able to produce four types of reflection: (a) technical reflection, (b) reflection on action, (c) deliberative reflection, and (d) personalistic reflection. In addition, almost half the entries that were defined as descriptive reflection and dialogic reflection were analytic. Based on the research results, the author concluded that the use of the reflective journal is useful as a tool for transforming preservice teachers into reflective practitioners. The study concludes with a suggestion for cultivating reflection in preservice teachers in teacher education programs.